PENENTUAN INDEKS MONSUN INDONESIA BERDASARKAN ANGIN ZONAL - Yulihastin, Erma (Teknologi Indonesia, 2011)
The research defi ned monsoon index which represented Indonesia Maritime Continent. Indonesia monsoon index were calculated based on monthly mean zonal wind at 850 milibar over the north-east area (2-80N, 95-1180E) and south (2-100LS, 105-1500BT), mentioned as Index I and Index II, respectively. The choice of index area based on prevailing westerly(easterly) to easterly(westerly) wind in the annual cycle. Monthly mean wind data derived from NOAA Satellite (National Oceanic and Atmospheric Administration), NCEP/NCAR Reanalysis (National Center for Environmental Prediction/National Center for Atmospheric Research), which have 2.5 degree spatial resolution from 1948 to 2010. The results showed Index I and II have symmetry pattern. Maximum (> 5 m/s) of Index I occurred on August and minimum (<-4 m/s) occurred on January. Conversely, Index II reached maximum (> 5m/s) at February and the minimum (<-5 m/s) occurred on August. The Index I and AUSMI (Australia Monsoon Index) were symmetry, but have different in amplitude. Correlation between the Index I and AUSMI were 0.99. The Index II and Webster-Yang Index were symmetry but have different in phase and amplitude. Correlation between the Index II and Webster-Yang Monsoon Index were also 0.99. Correlation between index I(II) and precipitable water were 0.68(0.95), respectively.